A sociological analysis of phonics lesson plans across four structured pedagogic programmes in South Africa - Boyd, Colleen (School of Education, 2023)
Nationally, there has been widespread acceptance that South Africa's schooling system faces a literacy crisis. In response to this, school improvement efforts have taken the form of structured pedagogic programmes – “a triple cocktail” of interventions that offer teacher training, resource provisioning and lesson plans in an attempt to alter teacher's pedagogy and improve learning outcomes. Focusing on lesson plans (also referred to as teacher guides) that attempt to structure phonics pedagogy, this study uses a Bernsteinian framework located in the sociology of education to analyse the various ‘controls' the lesson plans place on pedagogy. It considers how these controls relate to the literature on effective phonics instruction as presented by the International Literacy Association. In addition, the study considers the various controls alongside an analysis of the level of scripting within each case, locating the discussion within current debates on the appropriate degree of scripting in lesson plans. The study finds that there are differences between the lesson plans in terms of the controls offered particularly as these relate to notions of effective phonics instruction and levels of scripting. In conclusion, this research argues for expanded lesson plans that further exteriorise the phonics curriculum by offering more explicit evaluative criteria and increased scripting that further supports teachers in enacting effective, and contextualised, phonics programmes.